Derivational Affixes Analysis of Emma Watsonâ€™s UN Speech on Gender Equality 2014 - Muhamad Eginda Erlangga (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
This research is entitled â€œDerivational Affixes Analysis of Emma Watsonâ€™s UN Speech on Gender Equality 2014â€. The data source of this research is taken from the transcript of Emma Watsonâ€™s speech. The method used to analyze the data is quantitative and qualitative descriptive methods. The objectives of this research are to investigate the derivational affixes, particularly the types of the derivational affixes and the function of derivational affixes. The result of the study demonstrated 60 affixes and obtained prefix (1) and suffix (59). Those affixes are im- (1), -ism (1), -ist (1), -dom (1), -ify (1), -ce (1), -ful (1), -ment (1), -able (1), -tion (2), -er (2), -ness (2), -al (2), -ive (2), -ous (2), -y (3), -ize (3), -ity (4), -ing (4), -ion (4), -d (4), -ly (7), and -ed (10). These affixes are identified based on their function as noun maker, verb maker, adjective maker, and adverb maker. The result shows the data of adjective maker (43.3%), noun maker (36.7%), adverb maker (11.7%), and verb maker (8.3%).